Tumor mutational burden as a pan-cancer biomarker for immunotherapy: the limits and potential for convergence - Passaro, Antonio; Stenzinger, Albrecht; Peters, Solange (Cancer cell, 2020)
A recent study in The Lancet Oncology reports that high tumor mutational burden (TMB) is associated with response to anti-PD-1 pembrolizumab, leading to the second FDA approval of a tissue-agnostic predictive biomarker for immunotherapy in solid tumors. This is a step forward in realizing the full potential of cancer immunotherapy.